PROBLEMS AND PROSPECTS OF HYDRAULIC MODELLING FOR ENVIRONMENTAL FLOWS ASSESSMENT STUDIES IN EAST AFRICA - Ndomba, Preksedis M; Nobert, Joel (Tanzania Journal of Engineering and Technology, 2017)
The objective of this paper is to document the problems and prospects of hydraulic modelling for Environmental Flows Assessment (EFA) studies based on selected case studies. Most of studies in East Africa use Holistic methodologies. An ideal data set for defining river hydraulics for most of these methods would be six data points of stage measurements over a good distribution of discharges, the stage of zero discharge and some flood-related data. Besides, in East African region EFA studies suffer from data scarcity (i.e., poorly gauged sites) and limited expertise and funding. The hydraulics studies conducted by the authors entailed desktop research, limited fieldwork for data collection, data analysis, and modelling. The hydraulic models (HEC-RAS and PHABSIM) used are governed by Manning and/or Energy equation(s) to simulate hydraulics. The optimized sensitive parameters include roughness number, expansion/contraction coefficients, roughness modifier and Beta coefficient. Data collected at medium flow, bank full discharge information at neighbouring flow gauging stations, information from previous studies, field observations on flow regimes and professional experience validated the performance of these models. The geometric characteristics for extended floodplains and/or swamps were derived from a calibrated NASA Shuttle Radar Topographic Mission (SRTM) Digital Elevation Models (DEM) of 30 arc-seconds resolution under HEC-GeoRAS GIS extension Environment. The modelling results were considered satisfactory because the relative errors for most of applications fall below 20%. The good performance achieved is attributed to the instituted quality control measures right from suitable sites selection to hydraulic modelling phases. Modelling results confidence rating of above 3 in a scale of 1 to 5 achieved depended upon the hydraulic complexity. Based on the satisfactory results in the case studies, the authors would like to note that there are some prospects of carrying out hydraulic analysis in the regions with inadequate data. However, professional input is the key to successful modelling exercises. Therefore, follow research should use more data to verify the approach adopted.